“Accomplishing something important:” exploring how parents of two-year-old children perceive the transition between child care classrooms - Morris, Emilee (Kansas State University, 2015)
For young children and their families, transitions between classrooms are a normative part of the child care experience, yet these types of transitions are seldom studied. In the United States, there are approximately 144,000 child care centers for children birth to five years of age (Child Care Aware, 2014). Nearly 60% of infants and toddlers participate in some form of nonparental child care arrangement (Iruka & Carver, 2006). In particular, how parents experience their child’s transitions between classrooms within child care centers is not well understood. Children aged birth to three years face challenges when separating from trusted caregivers and forming new relationships. This study explored the unfolding of perceptions of five families as their children turned two-years-old and moved between a one-year-old to a two-year-old classroom in the same child care setting. Drawing from a systems approach, the parental perception of the transition was examined in relation to their children’s experience. Structured interviews took place with families before, during, and after their children’s transition to the new classroom. Mothers were interviewed in four out of the five cases, and one couple chose to participate in the interviews together. Families reported unique concerns such as worry regarding the child’s adjustment or concern about how the child would be accepted in the new peer environment, based on certain factors of influence including past experiences with transitions and the temperament and behavior of their child in the child care setting. However, parents regarded the transition positively due to the perceived benefits of a classroom with older peers and advanced learning opportunities. Parents expressed this positive viewpoint to their children through conversations. Interviews suggested that the way parents perceived the transition was closely connected to the child’s behaviors in the new environment as well as the quality of relationships formed with the teachers and peers. The findings indicate the importance of individualizing the transition experience for families, remaining mindful of the family system during the transition, and implementing strategies to support the relationship building process. Keywords: qualitative, transitions, two-year-old, early childhood education, parents
Keywords: Early childhood education; Transitions; Two-year olds; Teacher education; Parents